ANALISIS RANCANG BANGUN EPISTEMOLOGI MULLĀ ṢADRĀ
There were at least four schools before the Mullā Ṣadrā era, namely peripatetic, illumination, ‘irfa>n, and kala>m. These four schools reached common ground in a school of thought which became known as al-H